Spatial distribution of cliff plant species in the Balearic Islands under current and projected climatic scenarios - Borràs, Joshua; Cortés-Fernández, Iván; Capó, Miquel (Basic and applied ecology, 2024)
Cliff ecology has been studied for decades, providing information about its high biodiversity values and their vulnerability to climate change. Also, insular ecosystems present biodiversity hotspots with high endemicity, but they are also severely affected by anthropogenic effects. Together, insular cliff communities combine both biodiversity uniqueness and high vulnerability to global change, but few studies have evaluated these particular ecosystems. Our aim was to provide information on the spatial distribution of insular cliff-specific vegetation assessing which environmental and climatic variables contribute to the definition of cliff habitat conditions. Ecological niche modelling for cliff populations in Balearic Islands has been calculated with presences of 20 plant species and climatic and geographical variables using a Random Forest model. The most important climatic variables for the model generation were mean temperature of the driest quarter and precipitation of the coldest quarter. The map obtained showed that mountain ranges from all islands provide highly suitable conditions for rupicolous species. Both the pessimistic and optimistic models showed that the habitat suitability of cliff vegetation in the mountain ranges would decrease, while they are close to zero in lowlands for the period 2021–2040. This study emphasizes the vulnerability of cliff habitats to climate change due to their limited dispersal capacity and distribution and the strict requirements for habitat suitability. From this work, future studies can focus on single-species analysis to evaluate if any cliff specialist species can be at risk of extinction due to climate change.